A case of McCune-Albright syndrome associated with Gs alpha mutation in the bone tissue - GÖZÜ, HÜLYA (JAPAN ENDOCRINE SOC, 2006)
The syndrome of McCune-Albright syndrome (MAS) is clasically defined as a triad presentation with the findings of polyostotic fibrous dysplasia, cafe-au-lait spots, and sexual precocity. However, not all patients present with complete symptoms. A 52-year-old mail was diagnosed as having a variant of McCune-Albright syndrome with the following findings: polyostotic Fibrous dysplasia, acromegaly due to pituitary tumor and subclinical hyperthyroidism due to toxic multinodular goiter. Sexual precocity and cafe-au-lait spots were not noted. Acromegaly was confirmed by laboratory examination (IGF-1, glucose Suppression test and TRH stimulation test). Long acting somatostatin analogue was used as treatment. Although the pituitary tumor Could not be removed due to technical problems, mass lesions on the cranium were removed subtotally. Histopathological evaluation demonstrated that the lesion complied with fibrous dysplasia. Genomic DNAs were isolated from the craniofacial bones and peripheral leucocytes of the patient. After amplifying the related regions, Gs alpha (Gs alpha) gene was analysed by automatic DNA sequence analysis. Ail activating mutation of the Gs alpha gene (Arg 201 Cys) was found in the genomic DNA isolated from the bone tissue of the patient, but not in the genomic DNA isolated from the blood. We described a case of MAS associated with Gs alpha mutation in the bone tissue, presenting with polyostotic fibrous dysplasia, subclinical hyperthyroidism and acromegaly.
Keywords: McCune-Albright syndrome; acromegaly; Gs alpha mutation; POLYOSTOTIC FIBROUS DYSPLASIA; SECRETING PITUITARY-ADENOMA; STIMULATORY G-PROTEIN; ACTIVATING MUTATION; GROWTH-HORMONE; GNAS1 GENE; G(S)ALPHA MUTATION; CUSHINGS-SYNDROME; CELLS; PIGMENTATION